Stereotactic Body Radiation Therapy (SBRT) for Prostate Cancer in Men With a High Baseline International Prostate Symptom Score (IPSS ≥ 15) - Aghdam, Nima; Pepin, Abigail; Buchberger, David; Hirshberg, Jason; Lei, Siyuan; Ayoob, Marilyn; Danner, Malika; Yung, Thomas; Kumar, Deepak; Collins, Brian T.; Lynch, John; Kataria, Shaan; et al. (Frontiers in Oncology, 2020)
Background: Patients with a high pretreatment IPSS may have higher rates of late urinary morbidity after radiation therapy for prostate cancer (1). Stereotactic body radiation therapy (SBRT) delivers fewer high-dose fractions of radiation, which may be radiobiologically favorable to the conventional low-dose external beam fractions. The urinary toxicity associated with SBRT, however, remains unclear in patients with a high IPSS (1). We report our experience using SBRT for localized prostate cancer in patients with pretreatment IPSS ≥ 15. Methods: Localized prostate cancer patients with a pre-treatment IPSS ≥ 15 treated with SBRT at Georgetown University Hospital from 2009 to 2016 were included in this retrospective review of prospectively collected data. These patients were treated to 35–36.25 Gy in five fractions delivered via CyberKnife (Accuray Inc., Sunnyvale, CA). Urinary toxicity was assessed using the Common Terminology Criteria for Adverse Events version 4.0 (CTCAE v4). Urinary quality of life was assessed using validated questionnaires (IPSS and EPIC-26). Results: 53 patients at a median age of 71 years (range 57–89 years) received SBRT with a minimum follow up of 3 years. The median prostate size was 37 cm3 (range 12–100 cm3) and 30.2% patients received ADT. The 3-years incidence rate of Grade 3 urinary toxicity was 7.5% with median time to toxicity of 2.9 years. There were no Grade 4 or 5 toxicities. A mean baseline IPSS score of 19.8 significantly decreased to 12.9 at 3 months post-SBRT (p = 0.002) and remained stable at 36 months (13.7). A mean baseline EPIC-26 obstructive/irritative score of 64.1 significantly improved to 80.2 at 3 months (p = 0.002). This improvement was maintained to 36 months. There was no significant change from the mean baseline EPIC-26 urinary incontinence score at any point during follow up. Conclusions: SBRT for clinically localized prostate cancer was well-tolerated in men with baseline IPSS ≥ 15 (1). Grade 3 toxicities occurred but resolved with time. Our data suggest that poor baseline urinary function does not worsen following SBRT and may even improve. High baseline IPSS score should not be considered a contraindication to SBRT.